Investigation of Antioxidant Activities of Melissa officinalis and Lavandula angustifolia Extracts against Chromium Induced Oxidative Damage in Saccharomyces cerevisiae with Molecular Biological and Biochemical Biomarkers - Beyaz, Seda (Progress in Nutrition, 2022)
Melissa and Lavandula are known to exhibit high antioxidant and strong biological activities thanks to their rich polyphenol and aromatic content. In this study, eight groups were created to investigate whether Melissa and Lavandula have a protective role against chromium damage in Saccharomyces cerevisiae (S. cerevisiae). Application groups: (i) Control Group; (ii) Chromium (30 mM); (iii) Melissa (20%); (iv) Lavandula (20%); (v) Melissa (20%) + Lavandula (20%); (vi) Melissa (20%) + Chromium (30 mM); (vii) Lavandula (20%) + Chromium (30 mM); (viii) Melissa (20%) + Lavandula (20%) + Chromium (30 mM). S. cerevisiae cultures were grown at 30 °C for 1, 3, 5 and 24 hours. Cell growth, malondialdehyde (MDA) analyzes, glutathione (GSH) levels, catalase (CAT) activities were determined by spectrophotometer. Total protein concentrations were determined by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and bradford method. According to the results, when compared with the chromium group, cell growth (1, 3, 5 and 24 hours), total protein synthesis, GSH level (24 hours) and CAT level (24 hours) increased in Melissa, Lavandula and Melissa + Lavandula while MDA level (24 hours) decreased. Melissa and Lavandula plant extracts, which are rich in polyphenolic compounds, were found to provide antioxidant protection and reduce oxidative damage in S. cerevisiae culture. Thus, it is thought that it will contribute to new treatment methodologies by providing effective protection in the treatment of many diseases thanks to its strong antioxidant and antiinflammatory properties.